Succession of Internal Sulfur Cycles and Sulfur-Oxidizing Bacterial Communities in Microaerophilic Wastewater Biofilms - Okabe, Satoshi (American Society for Microbiology, 2005)
The succession of sulfur-oxidizing bacterial (SOB) community structure and the complex internal sulfur cycle occurring in wastewater biofilms growing under microaerophilic conditions was analyzed by using a polyphasic approach that employed 16S rRNA gene-cloning analysis combined with fluorescence in situ hybridization, microelectrode measurements, and standard batch and reactor experiments. A complete sulfur cycle was established via S(0) accumulation within 80 days in the biofilms in replicate. This development was generally split into two phases, (i) a sulfur-accumulating phase and (ii) a sulfate-producing phase. In the first phase (until about 40 days), since the sulfide production rate (sulfate-reducing activity) exceeded the maximum sulfide-oxidizing capacity of SOB in the biofilms, H(2)S was only partially oxidized to S(0) by mainly Thiomicrospira denitirificans with NO(3)(−) as an electron acceptor, leading to significant accumulation of S(0) in the biofilms. In the second phase, the SOB populations developed further and diversified with time. In particular, S(0) accumulation promoted the growth of a novel strain, strain SO07, which predominantly carried out the oxidation of S(0) to SO(4)(2−) under oxic conditions, and Thiothrix sp. strain CT3. In situ hybridization analysis revealed that the dense populations of Thiothrix (ca. 10(9) cells cm(−3)) and strain SO07 (ca. 10(8) cells cm(−3)) were found at the sulfur-rich surface (100 μm), while the population of Thiomicrospira denitirificans was distributed throughout the biofilms with a density of ca. 10(7) to 10(8) cells cm(−3). Microelectrode measurements revealed that active sulfide-oxidizing zones overlapped the spatial distributions of different phylogenetic SOB groups in the biofilms. As a consequence, the sulfide-oxidizing capacities of the biofilms became high enough to completely oxidize all H(2)S produced by SRB to SO(4)(2−) in the second phase, indicating establishment of the complete sulfur cycle in the biofilms.